Evaluation of vegetation size and its relationship with septic pulmonary embolism in tricuspid valve infective endocarditis: A real time 3DTEE study. Issue 4 (18th February 2017) - Utsunomiya, Hiroto; Berdejo, Javier; Kobayashi, Sayuki; Mihara, Hirotsugu; Itabashi, Yuji; Shiota, Takahiro
Abstract : Background: Tricuspid valve infective endocarditis (TVIE) causes septic pulmonary embolism (PE). However, the impact of vegetation size on PE is not fully elucidated. Methods: In 26 consecutive patients with definite TVIE according to Duke criteria, we tested clinical, microbiological, and echocardiographic data including real time three‐dimensional transesophageal echocardiography (3DTEE) as potential predictors of PE. 3DTEE measurement of maximum length of vegetation (MLV) was obtained with Advanced QLAB Quantification Software by cropping the 3D volume with the appropriate 2D plane to obtain the largest value. The standard two‐dimensional transesophageal echocardiography (2DTEE) images were also evaluated to determine the MLV. Results: Pulmonary embolism occurred after TVIE diagnosis with 3DTEE assessment and initiation of antibiotic therapy in 12 patients (46.2%). The 3DTEE MLV was larger than the 2DTEE value with a mean difference of 3.6 mm (95% CI, 2.5–4.6 mm). The best cutoff value for prediction of PE was MLV ≥16.4 mm with 3DTEE and MLV ≥9.5 mm with 2DTEE. The positive predictive value increased from 76.9% to 90% when 3DTEE was used. The accuracy of classification of patients with PE increased from 80.6% to 84.9% with 3DTEE. On multivariate analysis, 3DTEE MLV ≥16.4 mm (odds ratio 20.5; 95% confidence interval 1.31–322; P =.031) was independently associated with the occurrence of PE after adjustment for age, sex, complex vegetation, and the number of vegetation‐attached leaflets. Conclusions: In TVIE, vegetation length is a strong predictor of the occurrence of PE. In combination with 2DTEE, 3DTEE may identify high‐risk patients who will need a more aggressive therapeutic strategy.